Micronanoparticles and micronanoparticle solutions
Patent Information
- Application Number
- JP2026176400
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-07-17
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-16
Smart Images

Figure 2026169264000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to ultrafine nanoparticles and ultrafine nanoparticle solutions.
Background Art
[0002] Nanoparticles of metals, metalloids, semiconductors, and compounds are materials whose industrialization is being advanced in various fields such as environment, IT, printing, and medical care, as catalysts, magnetic materials, battery materials, optoelectronic materials, semiconductor materials, medical materials, pharmaceutical materials, and health foods. Nanoparticles are superior in surface area, reactivity, catalytic properties, magnetism and the like compared to bulk bodies and powders.
[0003] Conventional techniques for producing nanoparticles include chemical synthesis methods, sol-gel methods, laser ablation methods, plasma irradiation methods, atomization methods, injection methods, mechanical milling, CVD, PVD, and plasma methods. In plasma methods, methods for generating plasma include methods using discharge phenomena such as arc discharge, corona discharge, glow discharge, streamer discharge, and spark discharge, as well as methods using microwaves, and wire explosion methods are also included therein. Among these, repeated spark discharge in liquid is used herein. However, the conventional methods have the drawback that nanoparticles tend to aggregate easily. In addition, the particle size is large except for the chemical synthesis method. To address this problem, for example, the use of glow discharge in liquid as described in Patent Documents 1 and 2 can be considered. The present inventors have also disclosed Non-Patent Documents 1 to 5 and the like regarding the production of nanoparticles using spark discharge in liquid.
[0004] For example, gold nanoparticles, a type of metal nanoparticle, have long been used as a staining material for stained glass and other applications, and more recently as a biostaining agent for transmission electron microscopy. In the medical field, gold nanoparticles are used in DNA sensors, in vivo cancer research, nanotoxicology, intracellular probes, optical tweezers, and DNA analysis. They are used for biosensing by utilizing their affinity with living organisms, and for gene delivery by coating them with highly biocompatible polymers. Medical nanoparticles used in cancer treatment and diagnostics are required to pass between cells and inside cells, and to incubate with DNA, requiring smaller sizes.
[0005] Platinum, palladium, silver, and copper nanoparticles are widely used as antibacterial materials in medicine, health foods, and cosmetics. Platinum is also used as an anticancer agent. Both platinum and palladium have been approved by the Ministry of Health, Labour and Welfare as safe food additives.
[0006] The development of catalysts using small-particle nanoparticles of platinum (Pt), rhodium (Rh), palladium (Pd), and other materials is a critical issue related to industrial infrastructure such as the environment, resources, and energy. In particular, the development of high-performance precious metal catalysts is an urgent task in semiconductor manufacturing, exhaust gas catalysts, and fuel cell catalysts due to their rarity and importance. Platinum is also used as a catalyst in the electrolysis of water. Creating small-particle nanoparticles is essential to addressing this challenge.
[0007] The liquid containing dispersed nanoparticles discussed here is called a dispersed colloid.
[0008] Generally, dispersed colloidal particles universally possess van der Waals forces, which are the sum of intermolecular forces and are synonymous with surface tension. On the other hand, a potential difference exists on the surface of dispersed particles due to the difference in composition and the polarity of the solvent, and a diffusive electrical bilayer is formed by counterions with the opposite sign to the surface potential. Since particles of the same type have the same type of counterion bilayer, when particles approach each other, the bilayers overlap, and an osmotic repulsion force is generated by the entropic effect originating from ion diffusion, preventing particle aggregation and stabilizing the dispersion system. In the classification of dispersed colloids using water as the dispersion medium, those that easily precipitate when an electrolyte is added are sometimes called hydrophobic colloids, and those that do not precipitate easily are called hydrophilic colloids. In the case of hydrophilic colloids, they have a surface charge similar to hydrophobic colloids, and many water molecules are coordinated by hydration (solvation), and they are further stabilized by the steric repulsion of these molecules.
[0009] Gold colloids are colloids in which gold nanoparticles are dispersed in a fluid. The color varies depending on the state of the liquid, but for particles of about 10 nm, they are generally red; as the particle size decreases, they become pale yellow; as the particle size increases, they become purple to pale blue; and above 100 nm, they become a cloudy yellow. Gold colloids have unique optical and electrical properties and are used in electron microscopy, electronics, nanotechnology, and materials science. [Prior art documents] [Patent Documents]
[0010] [Patent Document 1] Japanese Patent Publication No. 2012-167335 [Patent Document 2] Japanese Patent Publication No. 2019-094541 [Non-patent literature]
[0011] [Non-Patent Document 1] “Homogeneously alloyed nanoparticles of immiscible Ag-Cu with ultrahigh antibacterial activity”, L. Yang, L. Chen, YC Chen, L. Kang, J. Yu, Y. Wang, C. Lu, T. Mashimo, A. Yoshiasa, CH Lin, Colloids and Surfaces B: Biointerfaces 180, 466-472 (2019).
Outdoor Tool2
Outdoor Tools3
Outdoor Tools 4
[0012] In the field of catalysts, high-performance catalysts such as platinum (Pt), rhodium (Rd), and palladium (Pd) are important because they relate to industrial infrastructure such as the environment, resources, and energy. In particular, the development of high-performance precious metal catalysts is an urgent issue in exhaust gas catalysts and fuel cell catalysts due to their rarity and importance, and the nanoparticles of the present invention are useful in addressing this issue. In catalysts, it is said that the smaller the particle size, the greater the surface area and the higher the catalytic properties.
[0013] Platinum, palladium, silver, and copper nanoparticles are widely used as antibacterial materials in medical, health food, and cosmetic ingredients. When antibacterial materials are used on humans, small nanoparticle sizes are required.
[0014] In the medical field, gold nanoparticles are used in DNA sensors, in vivo cancer research, nanotoxicology, intracellular probes, optical tweezers, and DNA analysis. Their biocompatibility is utilized for bisensing, and they are coated with highly biocompatible polymers for gene delivery. Medical nanoparticles used in cancer treatment and diagnostics require smaller sizes to pass between cells and inside cells, and to incubate with DNA.
[0015] Nanoparticles are also used as catalysts, and the smaller the size, the larger the surface area and the greater the catalytic effect, so smaller sizes are in demand. For example, palladium nanoparticles are used in semiconductor plating. In particular, catalysts used in IC and LSI semiconductors need to penetrate between the various elements that make up the integrated circuit and exert their catalytic properties. This inter-element distance is currently about 10 nm, and to improve the performance of IC and LSI semiconductors, there is a demand for palladium nanoparticles that are even smaller, about 2 nm or less.
[0016] Furthermore, ferromagnetic nanoparticles are used in cancer treatment by utilizing the heating effect caused by electromagnetic activity. Fe, Co, and Ni are commonly used in this treatment. If even smaller nanoparticles can be obtained, they can easily penetrate cells, which is expected to significantly increase their effectiveness.
[0017] Thus, there is a demand for the production of smaller metal nanoparticles for catalytic, medical, and health food applications. Chemical reduction methods are used for this purpose, but there are limitations to the particle size they can produce. Furthermore, nanoparticles require a well-dispersed, uniform composition and uniform particle size, but methods such as arc discharge, vapor deposition (CVD, PVD), and reduction methods generate aggregates with large particle sizes, and suppressing this is difficult. [Means for solving the problem]
[0018] The inventors of this invention have conducted extensive research to solve the above problems and have found that the following invention is suitable for the above purpose, leading to the present invention. That is, the present invention relates to the following invention.
[0019] <b1>Extremely small gold-containing nanoparticles with an average particle size of less than 0.6 nm, as measured by dynamic light scattering. <b2>These are extremely small palladium-containing nanoparticles with an average particle size of 1.4 nm or less, as measured by dynamic light scattering. <b3>These are extremely small palladium-containing nanoparticles with an average particle size of 1.7 nm or less, as measured by dynamic light scattering. <b4>An ultrafine nanoparticle containing platinum, having an average particle diameter of 1.4 nm or less as measured by a dynamic light scattering method. <b5>Extremely small nanoparticles having an average particle size of 2.0 nm or less as measured by dynamic light scattering, and containing one of the materials selected from the group consisting of metals, semimetals, and semiconductors. <b6>The average particle size of the aforementioned ultrafine nanoparticles is 1.5 nm or less. <b5>The extremely small nanoparticles described above. <b7>The metal is a noble metal, a base metal, an alloy, or a compound. <b5>or <b6>The extremely small nanoparticles described above.
[0020] <c1> <b1> ~ <b7>An ultrafine nanoparticle solution in which the nanoparticles according to any one of the preceding items are dispersed in a solvent.
[0021] [Spark discharge definition] Spark discharge, also referred to as spark discharge in English, is a phenomenon where a spark is observed between electrodes when the voltage exceeds a certain limit, and refers to the case of a discontinuous transient phenomenon. When the voltage applied between the electrodes is increased, molecules present between the electrodes collide with electrons accelerated by the high voltage and are ionized (referred to as alpha action), and secondary electron emission that occurs when positive ions generated by the ionization collide with the negative electrode supplies electrons from the negative electrode into the space between the electrodes (referred to as gamma action). When the amount of charged particles generated by these two actions is greater than the amount lost to both electrodes or the surrounding space, the amount of charged particles flowing between the electrodes increases avalanche-like, which occurs as a large current flows between the electrodes.
[0022] Here, the rise time or fall time refers to the respective time required for the current to rise from 10% to 90% of the peak value, or for the current to fall from 90% to 10% of the peak value. [Advantageous Effects of Invention]
[0023] According to the present invention, ultrafine nanoparticles and an ultrafine nanoparticle solution that exhibit excellent physical properties in various applications can be obtained. [Brief Description of Drawings]
[0024] [Figure 1] This is a diagram illustrating an example of the schematic configuration of a nanoparticle production apparatus used in the method for producing nanoparticles according to one embodiment of the present invention. [Figure 2] This is a diagram for explaining the circuit diagram of a power supply. [Figure 3] This is a diagram showing an example of a voltage waveform generated by the power supply (2). [Figure 4A] This is a diagram showing an example of a current waveform when a palladium electrode is used. [Figure 4B] This is a diagram showing an example of a current waveform when a palladium electrode is used. [Figure 4C] This figure shows an example of a current waveform when using a palladium electrode. [Figure 4D] This figure shows an example of a current waveform when using a palladium electrode. [Figure 4E] This figure shows an example of a current waveform when using a palladium electrode. [Figure 5A] This is a photograph of a glass container holding a liquid containing palladium nanoparticles. [Figure 5B] This is a photograph of a glass container holding a liquid containing palladium nanoparticles. [Figure 5C] This is a photograph of a glass container holding a liquid containing palladium nanoparticles. [Figure 5D] This is a photograph of a glass container holding a liquid containing palladium nanoparticles. [Figure 6A] This is the result of observing palladium nanoparticles using FE-TEM. [Figure 6B] This is the result of observing palladium nanoparticles using FE-TEM. [Figure 6C] This is the result of observing palladium nanoparticles using FE-TEM. [Figure 6D] This is the result of observing palladium nanoparticles using FE-TEM. [Figure 6E] This is the result of observing palladium nanoparticles using FE-TEM. [Figure 7A] This is the result of measuring the particle size of palladium particles using dynamic light scattering. [Figure 7B] This is the result of measuring the particle size of palladium particles using dynamic light scattering. [Figure 7C] This is the result of measuring the particle size of palladium particles using dynamic light scattering. [Figure 7D] This is the result of measuring the particle size of palladium particles using dynamic light scattering. [Figure 7E] This is the result of measuring the particle size of palladium particles using dynamic light scattering. [Figure 7F] This is the result of measuring the particle size of palladium particles using dynamic light scattering. [Figure 7G] This is the result of measuring the particle size of palladium particles using dynamic light scattering. [Figure 7H] This is the result of measuring the particle size of palladium particles using dynamic light scattering. [Figure 8A] This figure shows an example of a current waveform when using gold electrodes. [Figure 8B] This figure shows an example of a current waveform when using gold electrodes. [Figure 8C] This figure shows an example of a current waveform when using gold electrodes. [Figure 8D] This figure shows an example of a current waveform when using gold electrodes. [Figure 9A] This is a photograph of a glass container holding a liquid containing gold nanoparticles. [Figure 9B] This is a photograph of a glass container holding a liquid containing gold nanoparticles. [Figure 9C] This is a photograph of a glass container holding a liquid containing gold nanoparticles. [Figure 9D] This is a photograph of a glass container holding a liquid containing gold nanoparticles. [Figure 10A] This is the result of observing gold nanoparticles using FE-TEM. [Figure 10B] This is the result of observing gold nanoparticles using FE-TEM. [Figure 10C] This is the result of observing gold nanoparticles using FE-TEM. [Figure 11A] This is the result of measuring the particle size of gold nanoparticles using dynamic light scattering. [Figure 11B] This is the result of measuring the particle size of gold nanoparticles using dynamic light scattering. [Figure 11C] This is the result of measuring the particle size of gold nanoparticles using dynamic light scattering. [Figure 11D] This is the result of measuring the particle size of gold nanoparticles using dynamic light scattering. [Figure 11E] This is the result of measuring the particle size of gold nanoparticles using dynamic light scattering. [Figure 11F] This is the result of measuring the particle size of gold nanoparticles using dynamic light scattering. [Figure 11G] This is the result of measuring the particle size of gold nanoparticles using dynamic light scattering. [Figure 11H] This is the result of measuring the particle size of gold nanoparticles using dynamic light scattering. [Figure 12A] This figure shows an example of a current waveform when using platinum electrodes. [Figure 12B] This figure shows an example of a current waveform when using platinum electrodes. [Figure 13A] This is the result of observing platinum nanoparticles using FE-TEM. [Figure 13B] This is the result of observing platinum nanoparticles using FE-TEM. [Figure 14A] This shows the particle size measurement results for platinum nanoparticles using dynamic light scattering. [Figure 14B] This shows the particle size measurement results for platinum nanoparticles using dynamic light scattering. [Modes for carrying out the invention]
[0025] The embodiments of the present invention will be described in detail below, but the description of the constituent elements described below is an example (representative example) of an embodiment of the present invention, and the present invention is not limited to the following unless its gist is changed. In the drawings, when the expression "~" is used, it is used to include the number before it but not the number after it. In this specification, when the expression "~" is used, it is used to include the numbers before and after it.
[0026] [Manufacturing method of the present invention] The present invention provides a manufacturing method that includes a spark discharge step in which repeated spark discharge is performed in a liquid between a pair of electrodes selected from the group consisting of metals, metalloids, semiconductors, elemental elements, alloys, and compounds, under discharge conditions of a peak current of 80A or more, preferably 100A or more or 125A or more, thereby forming nanoparticles in the liquid that contain any of the group consisting of metals, metalloids, semiconductors, elemental elements, alloys, and compounds, and thereby obtaining a nanoparticle-containing liquid containing the nanoparticles. According to the manufacturing method of the present invention, nanoparticles smaller than conventional methods (extremely small nanoparticles of 2.0 nm or less) can be efficiently manufactured.
[0027] [Damage nanoparticles] The nanoparticles of the present invention have an average particle size of 0.1 nm or more and 2.0 nm or less as measured by dynamic light scattering, and include any selected from the group consisting of metals, metalloids, semiconductors, elemental elements, alloys, and compounds.
[0028] The nanoparticles of the present invention are smaller in particle size than conventional nanoparticles and are efficiently produced. They are expected to have dramatically improved surface area, reactivity, catalytic properties, and magnetism, and can be used in dyes, catalysts, medical and pharmaceutical materials, health foods, magnetic materials, battery materials, photoelectric materials, semiconductor materials, quantum dots, and other applications not seen before.
[0029] The nanoparticles of the present invention can be manufactured by the manufacturing method of the present invention. The corresponding components in this application can be used interchangeably.
[0030] The present invention relates to a method for producing nanoparticles, which involves forming extremely small nanoparticles by performing repeated spark discharges in a liquid between two electrodes immersed in a liquid, and utilizes a special power supply. In this manufacturing process, each electrode is made of the target nanoparticle material, such as a single metal or an alloy bulk metal, and discharge is performed under discharge conditions that enable the synthesis of small-sized nanoparticles.
[0031] Regarding these discharge conditions, the rise and fall times of the current between the electrodes of the spark discharge are set to be steep, such as 10 μs or less and 20 μs or less, respectively. Furthermore, regarding these discharge conditions, it is preferable to use a peak voltage of approximately 160 V to 250 V, with the voltage rise and fall times each being 1 μs or less, and a peak current of 80 A or more, preferably 100 A or more or 125 A or more. It is also preferable to use a condition in which the voltage is periodically applied in a rectangular wave shape with a time width of 10 μs to 200 μs. In addition, it is preferable to repeatedly generate spark discharges at time intervals of 50 μs to 20 ms. We have found that this allows for the efficient synthesis of nanoparticles smaller than conventional methods. The present invention is based on these findings.
[0032] I. <Manufacturing of Nanoparticles> The manufacturing method of the present invention will be described below with reference to Figure 1, etc. Figure 1 shows an example of the schematic configuration of a manufacturing apparatus 10 used in the nanoparticle manufacturing method according to the first embodiment of the present invention. The manufacturing apparatus 10 includes, for example, electrodes 101 and 102, a liquid 202 contained in a container 201, and a power supply 30. It also includes a vibration device 40. The vibration device 40 can be omitted.
[0033] [Pair of electrodes 101, 102] The pair of electrodes 101 and 102 are electrodes for repeatedly generating spark discharges in the liquid 202. In the manufacturing apparatus 10, for example, one end of each electrode 101 and 102 is immersed in the liquid 202, while the other end of each electrode 101 and 102 is not immersed in the liquid 202 and is placed in the atmosphere. The ends of electrodes 101 and 102 that are immersed in the liquid 202 are arranged to face each other, for example, with a predetermined gap between them.
[0034] Electrodes 101 and 102 can be, for example, rod-shaped, needle-shaped, or plate-shaped. The sizes of electrodes 101 and 102 may be equal or different. Furthermore, electrodes 101 and 102 may be made of the same material or different materials. Increasing the discharge area by enlarging the electrodes, for example, can significantly increase production volume, making it suitable for mass production of nanoparticles. The discharge area can be enlarged without particular limitations, as long as the device structure and current control are feasible.
[0035] [Electrode material] Electrodes 101 and 102 are made of metal and / or metalloid or semiconductor electrical conductive materials. These electrodes 101 and 102 may be identical or different. For example, when obtaining particles of a single element, it is preferable to use the same electrode of the single element for both. When obtaining alloys or compounds, different electrodes may be used. When obtaining alloys or compounds, the same electrode of the alloy or compound may be used for both, or electrodes of single elements may be used and reacted with liquid 202.
[0036] [metal] In this invention, metals include elemental metals and alloys. Here, metals include those that are substantially composed of elemental metal elements such as noble metals and base metals, alloys that are substantially composed of these metal elements, and alloys that include nonmetallic elements that are present when forming alloys with these metal elements.
[0037] [Precious metals] In this invention, precious metals are defined as metals that satisfy the conditions of being rare and having difficulty forming compounds, or metals that have a higher positive electrode potential compared to a standard hydrogen electrode. Generally, there are eight precious metals: gold (Au), silver (Ag), platinum (Pt), palladium (Pd), rhodium (Rh), iridium (Ir), ruthenium (Ru), and osmium (Os). Furthermore, precious metals occur as elemental metals, have a low ionization tendency, do not react directly with acids, and are not easily oxidized in air. The precious metals used in this invention may include any of those selected from the group consisting of gold (Au), silver (Ag), ruthenium (Ru), rhodium (Rh), palladium (Pd), osmium (Os), iridium (Ir), platinum (Pt), and copper (Cu).
[0038] In particular, when precious metals are used as electrodes, it is easy to obtain nanoparticles consisting essentially of the elemental form of the precious metal used in the electrodes by using the same type of precious metal for both electrodes. For example, using gold electrodes will yield gold nanoparticles, using palladium will yield palladium nanoparticles, and using platinum will yield platinum nanoparticles.
[0039] Nanoparticles of precious metal elements (e.g., Au, Pt, Pd, Ru, Rh, or Ag, Cu, etc.) are particularly important as catalysts, medical materials, pharmaceutical materials, and health foods.
[0040] In the field of catalysts, high-performance catalysts such as platinum (Pt), rhodium (Rd), and palladium (Pd) are important because they relate to industrial infrastructure such as the environment, resources, and energy. In particular, the development of high-performance precious metal catalysts is an urgent issue in exhaust gas catalysts and fuel cell catalysts due to their rarity and importance, and the nanoparticles of the present invention are useful in addressing this issue.
[0041] Pt, Pd, and Ru are used as exhaust gas catalysts, Pt and its alloys are used as fuel cell catalysts, and elemental precious metals are used in hydrogen and oxidation reactions. In addition, Pd is used as a catalyst in the manufacturing process of IC and LSI semiconductors.
[0042] In catalysts, reducing particle size increases surface area, significantly improving reactivity and catalytic properties. Therefore, small-particle nanoparticles are useful.
[0043] [Base metal] In this invention, base metals are metals that have a greater ionization tendency than hydrogen (low stability) and are easily oxidized when heated in air, excluding the noble metals mentioned above. For example, alkali metals (lithium (Li), sodium (Na), potassium (K), rubidium (Rb), etc.), alkaline earth metals (calcium (Ca), strontium (Sr), barium (Ba), etc.), magnesium group elements (beryllium (Be), magnesium (Mg), zinc (Zn), etc.), aluminum group elements (aluminum (Al), gallium (Ga), indium (In)), rare earth elements (yttrium (Y), lanthanum ( These include elements such as La (Lanium), cerium (Ce), tin group elements (titanium (Ti), zirconium (Zr), tin (Sn), hafnium (Hf), lead (Pb), etc.), iron group elements (iron (Fe), cobalt (Co), nickel (Ni)), nitrate group elements (vanadium (V), niobium (Nb), tantalum (Ta)), chromium group elements (chromium (Cr), molybdenum (Mo), tungsten (W), etc.), and manganese group elements (manganese (Mn), rhenium (Re)).
[0044] [alloy] In the present invention, the alloy is a solid solution or intermetallic compound of two or more metallic elements or a metallic element and a nonmetallic element such as carbon, nitrogen, or silicon. As these metallic elements, the aforementioned noble metals and base metals can be used.
[0045] [Semimetal] Metalloids are elements that exhibit properties intermediate between metals and nonmetals. Metalloids include carbon, which forms graphite, and phosphorus, which forms black phosphorus. Other metalloids include boron, silicon, germanium, arsenic, antimony, tellurium, bismuth, polonium, and astasine. These elements in metalloids are the main constituent elements of nanoparticles, or they are constituent elements when forming alloys, compounds, and semiconductors.
[0046] [semiconductor] In this invention, a semiconductor is a material having an electrical conductivity intermediate between that of a conductor and an insulator. Examples include silicon, germanium, selenium, and compound semiconductors. Compound semiconductors include group II-VI semiconductors such as CdS, CdSe, CdTe, ZnS, ZnSe, CdS, and ZnO; group III-V semiconductors such as GaAs, InP, and GaN; group IV-VI semiconductors such as PbS and PbSe; group IV compound semiconductors such as SiC and SiGe; and chalcopyrite semiconductors such as group I-III-VI semiconductors such as CuInSe2. Semiconductors may also contain metalloids such as carbon.
[0047] [Container 201] Container 201 contains the liquid 202. Furthermore, in order to efficiently cool the liquid 202 in order to maintain the initial state around electrodes 101 and 102 and to make it easier to control the reaction conditions, the manufacturing apparatus 10 may be equipped with a mechanism for stirring the liquid 202 or creating a flow in the liquid 202.
[0048] [Liquid 202] Liquid 202 is used to perform a liquid-phase spark discharge using a pair of electrodes 101 and 102, and also to temporarily store the products generated by the liquid-phase spark discharge. Depending on the type of nanoparticles being manufactured, it may also serve as a material for the nanoparticles. The amount of liquid 202 is not particularly limited; it should be enough so that at least a portion of the pair of electrodes 101 and 102 can be present in the liquid 202. The amount of liquid 202 should be enough so that it does not scatter due to the liquid-phase spark discharge described later, and the diffusivity of liquid 202 is not lost due to the concentration of the products generated by the liquid-phase spark discharge. The temperature of liquid 202 during discharge is not particularly limited and can be adjusted as appropriate depending on the type of liquid 202 used.
[0049] Discharge is usually performed in the range of room temperature to 300°C. However, if the temperature of liquid 202 is too high, the vapor pressure of liquid 202 will increase, and if liquid 202 is a flammable liquid, there is a possibility of ignition due to the discharge. On the other hand, if the temperature of liquid 202 is too low, the viscosity of liquid 202 will increase, and the diffusibility of the product due to the spark discharge in the liquid may be impaired. Therefore, it is preferable to keep liquid 202 at a temperature that takes these factors into consideration. The upper limit of the temperature is preferably 200°C or lower, and more preferably 150°C or lower. The lower limit of the temperature is sufficiently easy to operate at room temperature or higher, but it may also be 30°C or higher, or 40°C or higher.
[0050] Liquid 202 is not particularly limited, and is not restricted as long as it does not affect the reaction for the formation of the target product. Liquid 202 may be a mixture of two or more compounds. Liquid 202 can be selected according to the composition of the target nanoparticles. For example, to obtain nanoparticles made of the material used for the electrodes, one can select a liquid 202 that exists as a reaction site and in which the elements constituting the liquid 202 are not involved in the nanoparticles. Alternatively, to obtain nanoparticles of alloys or compounds, one can use a liquid 202 that contains elements that react appropriately with elements derived from the electrodes by spark discharge or the like to form alloys or compounds.
[0051] Liquid 202 can be water, hydrogen peroxide solution, ammonia solution, oils, silicone oil, ionic liquids, carbon tetrachloride, halogen solutions, molten sulfur, molten selenium, molten tellurium, saturated hydrocarbons, aromatic hydrocarbons, alcohols, esters, ethers, etc.
[0052] For example, liquid 202 is preferably selected from the group consisting of water, alcohol, toluene, xylene, aqueous ammonia solution, sulfur, and carbon tetrachloride. Using these liquids may facilitate the synthesis of pure elemental nanoparticles from the electrode material. In particular, if reaction with the liquid is undesirable, it is desirable to use carbon tetrachloride or toluene.
[0053] Liquid 202 can be the following: Saturated hydrocarbons such as hexane, octane, decane, cyclohexane, and cyclooctane can be used. Aromatic hydrocarbons such as benzene, toluene, xylene, and naphthalene can be used. Alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol, propylene glycol, and 1,4-butanediol can be used. Esters such as methyl acetate, ethyl acetate, butyl acetate, methyl benzoate, and dimethyl phthalate can be used. Ethers such as tetrahydrofuran, tetrahydropyran, dipropyl ether, dibutyl ether, diethylene glycol, and tetraethylene glycol can be used.
[0054] Liquid 202 may be water, saturated hydrocarbons, aromatic hydrocarbons, or alcohols, taking into consideration the dispersion, flammability, and oxidizing properties of the resulting nanoparticles. For example, methanol or ethanol is more preferable. Furthermore, if synthesis is carried out at high temperatures or followed by annealing, high-temperature stable oils, silicone oils, or ionic liquids may be used as liquid 202.
[0055] Liquid 202 may be selected considering its constituent elements in order to form compounds from nanoparticles or to modify nanoparticles. For example, when liquid 202 is water, oxide nanoparticles can be efficiently obtained; when liquid 202 contains molten sulfur or sulfur, sulfide nanoparticles can be efficiently obtained; when liquid 202 contains molten chalcogenide elements such as Se and Te, chalcogenide compound nanoparticles can be efficiently obtained; and when liquid 202 is an alcohol, carbide or carbon-coated nanoparticles can be efficiently obtained. Furthermore, when liquid 202 is a saturated hydrocarbon, aromatic hydrocarbon, alcohol, halogen solution such as oxygen chloride, or sulfur, nanoparticles modified with carbon, halogen elements, sulfur, etc., can sometimes be efficiently obtained.
[0056] [Composition of nanoparticles] In the method of the present invention, nanoparticles such as individual metals, metalloids, semiconductors, alloys, and compounds can be synthesized using the elements that constitute electrodes 101 and 102, and the individual elements that constitute liquid 202.
[0057] When obtaining a single metal, by using a metal element with low reactivity for electrodes 101 and 102, and using a liquid 202 that is also unresponsive, conditions can be created that make it difficult for other elements to react, thereby obtaining nanoparticles with high purity of that single metal.
[0058] Furthermore, when obtaining alloys, alloys of any composition can be obtained by appropriately reacting electrodes 101 and 102 with liquid 202. These alloys can include so-called inmissible alloys, which are difficult to mix and manufacture under other manufacturing conditions.
[0059] Furthermore, by using elements contained in liquid 202 in the nanoparticles, it is also possible to obtain nanoparticles of alloys, as well as nanoparticles of compounds such as oxides, nitrides, sulfides, chalcogenide compounds, carbides, chlorides, and halogen compounds.
[0060] When synthesizing oxide nanoparticles, liquid 202 is used, for example, water or hydrogen peroxide solution. When synthesizing nitride nanoparticles, liquid 202 is used, for example, a nitrogen compound such as ammonia solution.
[0061] When synthesizing nanoparticles of chalcogen compounds such as sulfides, liquid 202 is used, for example, a chalcogen substance such as sulfur or selenium that is in a liquid state at high temperatures.
[0062] When synthesizing carbide nanoparticles or carbon-coated nanoparticles, liquid 202 can be, for example, alcohols or hydrocarbons.
[0063] When synthesizing halogen compound nanoparticles, liquid 202 can be, for example, bromine, oxalic acid, hydrofluoric acid, hydrochloric acid, iodine, halogen elements, or halogen compounds. Alternatively, to obtain alloys, it is also possible to use salts of alkali element compounds, or acids or salts containing alkali element compounds, as liquid 202. Furthermore, it is also possible to use salts of alkaline earth compounds, or acids containing alkaline earth compounds, as liquid 202.
[0064] In the manufacturing method of the present invention, not only can nanoparticles be made substantially from the elements used in the electrodes, but the nanoparticles can also be doped or modified on the surface with elements contained in liquid 202 (for example, oxygen, nitrogen, sulfur, selenium, carbon, bromine, fluorine, chlorine, or iodine). Furthermore, alkali metals, alkaline earth metals, and other metallic elements such as Na, Mg, K, and Ca can also be used in liquid 202 as appropriate to modify the surface of the nanoparticles.
[0065] In the manufacturing method of the present invention, not only can nanoparticles be made substantially from the elements used in the electrodes, but the nanoparticles can also be doped with or modified on the surface with noble metal elements contained in liquid 202 (e.g., gold, platinum, palladium, rhodium, ruthenium, silver, copper, etc.). In this case, a solution of halogen compounds or the like may be used as the liquid as appropriate.
[0066] Furthermore, in this embodiment, when the liquid 202 is a saturated hydrocarbon, aromatic hydrocarbon, alcohol, etc., a carbon film can be formed to coat the surface of the nanoparticles. When the surface of the nanoparticles is coated with a carbon film, the nanoparticles become non-toxic and can be formed with excellent biocompatibility. Therefore, nanoparticles coated with a carbon film are expected to be put into practical use in the medical field (for example, in the field of cancer treatment).
[0067] [Power supply device 30] The power supply unit 30 is a device that supplies current to the manufacturing apparatus 10 and adjusts the voltage and current. The power supply unit 30 is designed using a basic spark generator and resistors. There are two types of basic spark generators: a conventional older type and a newer type, which differ in voltage rise time and current values.
[0068] Power supply (1) in Figure 2 is a schematic diagram showing an example of an older type of power supply circuit. This pulse generator consists of a circuit with a thyristor and a capacitor, and an internal resistance of about 10Ω. It outputs a square wave current with a two-stage current rise, a rise and fall time of 20μs or less, and a peak current of about 5A to 50A. In this power supply, the rise time is long and it is multi-stage. The current in this circuit is used in the range of 0.1 to 5A on average over time.
[0069] Figure 2 shows a schematic diagram of a new type of power supply (2) suitable for the manufacturing method of the present invention. Figure 3 shows the voltage waveform produced by power supply (2). In power supply (2), the pulse generator that generates a square wave can be configured to output a voltage with a rise and fall time faster than power supply (1), of 0.5 μs or less, a width of 100 μs intervals, a peak voltage of 160 V to approximately 250 V, and a frequency of 5 kHz. With an internal resistance of approximately 2 Ω, it is possible to output a current with a rise and fall time of 20 μs or less for the current flowing between electrodes, and a peak current of 80 A to 125 A or more. At 50 A or less, the rise and fall time is 5 μs or less.
[0070] Regarding these discharge conditions, the rise and fall times of the current between the electrodes of the spark discharge are set to be steep, such as 10 μs or less and 20 μs or less, respectively. Furthermore, regarding these discharge conditions, it is preferable to use a peak voltage of approximately 160 V to 250 V, with the voltage rise and fall times each being 1 μs or less, and a peak current of 80 A or more, preferably 100 A or more or 125 A or more. It is also preferable to use a condition in which the voltage is periodically applied in a rectangular wave shape with a time width of 10 μs to 200 μs. In addition, it is preferable to repeatedly generate spark discharges at time intervals of 50 μs to 20 ms. We have found that this allows for the efficient synthesis of nanoparticles smaller than conventional methods. The present invention is based on these findings.
[0071] [Spark discharge] In the manufacturing method of the present invention, repeated spark discharge in liquid is performed between two electrodes. As a result, the electrode material instantaneously evaporates, entering a short-term ionized (plasma) state, and during cooling, each element condenses, allowing nanoparticles to be synthesized even under conditions that are easy to manufacture, such as room temperature. When a high potential difference is generated between electrodes 101 and 102, repeated spark discharge in liquid occurs between their ends.
[0072] When the spark discharge frequency is 5kHz, the temperature in the discharge region partially reaches 1000K to 50000K. Therefore, it is possible to melt, vaporize, or ionize (plasma-ify) metals that are difficult to melt. Also, the newer power supply has a higher current than the older power supply, resulting in extremely high temperatures.
[0073] Furthermore, because repetitive spark discharge in liquid is a spark discharge, the discharge is intermittent, and the area where the discharge occurs is sharp and localized. Therefore, the high temperature and high pressure caused by the discharge are concentrated in a narrow area, and even if the discharge continues for several hours, the rise in the temperature of liquid 202 can be suppressed.
[0074] When elements originating from the electrodes become plasma, elemental ions tend to bond with each other more easily. As a result, the short-term plasma state, combined with the rapid cooling effect of the surrounding liquid, allows for the synthesis of nanoparticles. This spark discharge also allows for the synthesis of nanoparticles of elemental metals, alloys, and compounds, depending on the combination of electrodes 101 and 102 and liquid 202.
[0075] [Current and Temperature] In the manufacturing method of the present invention, the peak current of the new power supply (2) is more than twice that of the old type (1), reaching 80A to 125A or more. Assuming that the resistance of the sample does not change, electrical energy is proportional to the square of the current, so the new type generates more than four times the energy of the old type in the sample. If we consider that all of this is converted into thermal energy, then since thermal energy is specific heat × temperature, if the specific heat does not change, the temperature will be calculated to be more than four times higher. However, in plasma, the electron specific heat increases as the temperature rises, so the temperature will be lower than that. On the other hand, since the resistivity of plasma is generally inversely proportional to the temperature raised to the power of (3 / 2), the current will be even larger, and it is also possible that the temperature will be higher. In any case, it is thought that the current will be at least twice as high as that of the old type power supply.
[0076] This rapid temperature increase allows the new power supply to generate plasma at a much higher temperature than the old one, resulting in the generation of a much larger number of ions. The higher the temperature, the greater the cooling effect from the surrounding liquid, promoting more uniform nucleation. The rapid cooling rate is more intense than with the old power supply, suppressing crystal growth and generating a large number of small clusters. The higher the temperature, the greater the cooling effect from the surrounding liquid, promoting more uniform nucleation, and the intense cooling effect suppresses crystal growth, resulting in a significantly larger number of small clusters. These clusters are then rapidly cooled and frozen, yielding a large quantity of extremely small nanoparticles.
[0077] [Peak current] In the manufacturing method of the present invention, the peak current is preferably 80A or more, 100A or more, or 125A or more. Further increasing the plasma temperature generates a large number of ions, and by increasing the rapid cooling rate to the extreme, the number of metal nucleation sites can be further increased, preventing crystal growth and further reducing the particle size. The peak current is 50A or less with older power supplies. However, by adopting a new type of power supply, it can be 80A to 125A or more. However, the current may decrease if the electrodes are in contact or welded together. Also, the current value depends on the type of electrode and the individual discharge phenomenon, so the current value is not necessarily proportional to the voltage.
[0078] The peak current may be 100A or more, 125A or more, or 150A or more. Furthermore, while there is no specific upper limit for the peak current, it may be set to 500A or less, 250A or less, or 200A or less as appropriate, depending on the need to maintain long rise and fall times, and from the perspective of circuit design and control.
[0079] The peak current width, frequency, rise time, and fall time of the spark discharge can be determined according to the voltage of the power supply unit 30 that performs the spark discharge, or according to various conditions in the manufacturing apparatus 10.
[0080] The present invention relates to a method for producing nanoparticles by performing repeated spark discharge in a liquid between two electrodes immersed in a liquid. Each electrode uses, for example, the bulk metal of the target nanoparticle, and a large current of 80A or more, preferably 100A or more or 125A or more, can be used to synthesize nanoparticles smaller than those previously produced, such as nano-sized or smaller.
[0081] [Vibration device 40] The manufacturing apparatus 10 may include a vibration device 40. The vibration device 40 applies vibration to electrodes 101 and 102. By applying vibration to electrode 20, the accumulation of precipitates formed on the surface of electrode 20 can be eliminated, and discharge can be performed efficiently. The vibration device 50 may apply vibration to electrode 20 periodically or intermittently. Vibration is not necessarily required.
[0082] In the manufacturing method of the present invention, nanoparticles are synthesized in a liquid, and if the synthesized nanoparticles are Brown particles, the synthesized nanoparticles tend to float in the liquid, thus preventing aggregation of the nanoparticles. Although the synthesized nanoparticles may settle in the liquid, aggregation of the nanoparticles is unlikely to occur even in this settling. Here, aggregation refers to the concept that nanoparticles bind to each other by van der Waals forces, making them difficult to separate by stirring. Thus, the manufacturing method of the present invention makes nanoparticle aggregation unlikely, and the nanoparticles can be used in a dispersed state in liquid 202. Furthermore, a surfactant may be used to prevent aggregation.
[0083] Furthermore, a solution in which nanoparticles formed by the above manufacturing method are dispersed in liquid 202 may be used as the nanoparticle product (nanoparticle solution). Alternatively, nanoparticles that have settled in liquid 202 may be separated and used as the nanoparticle product. One method for separating small and large nanoparticles in liquid 202 is a centrifugation step. Alternatively, when nanoparticles suspended in the solution settle naturally and a precipitate layer is formed in container 30, the supernatant liquid that forms in the solution (supernatant liquid of the solution) may be taken from container 30, and the extracted supernatant liquid may be used as the nanoparticle product (nanoparticle solution).
[0084] In this case, the nanoparticles do not aggregate and settle, but remain dispersed in the solution, which is thought to be a dispersed colloidal particle. Generally, dispersed colloidal particles universally possess van der Waals forces, which are the sum of intermolecular forces and are synonymous with surface tension. On the other hand, a potential difference exists on the surface of the dispersed particles due to the difference in composition and the polarity of the solvent, and a diffusive electrical bilayer is formed by counterions with the opposite sign to the surface potential. Since particles of the same type have the same type of counterion bilayer, when particles approach each other, the bilayers overlap, and an osmotic repulsion force is generated by the entropic effect originating from ion diffusion, preventing particle aggregation and stabilizing the dispersion system.
[0085] Furthermore, in the classification of dispersion colloids using water as the dispersion medium, those that easily precipitate upon the addition of an electrolyte are sometimes called hydrophobic colloids, and those that do not precipitate easily are called hydrophilic colloids. In the case of hydrophilic colloids, they have a surface charge similar to hydrophobic colloids, and many water molecules are coordinated through hydration (solvation), and they are further stabilized by the steric repulsion of these molecules. In addition, some hydrophilic colloids surround hydrophobic colloids to prevent coagulation, and colloids in this state are called protective colloids. Protective colloids may also be stabilized by the adsorption of proteins, etc., on their surface, which changes the surface potential.
[0086] [Surfactants] Nanoparticles in liquids tend to aggregate, forming larger particles that are no longer Brown particles and are prone to sedimentation. Surfactants are substances that have both a water-attracting part (hydrophilic group) and an oil-attracting part (lipophilic / hydrophobic group) within their molecule, and are often called amphiphilic molecules. They work by forming micelles, vesicles, and lamellar structures, thereby uniformly mixing polar and nonpolar substances. They also have the effect of weakening surface tension. As a result, nanoparticles can be dispersed in liquids without aggregation. This is effective in both water and oil. In the synthesis of nanoparticles using spark discharge, surfactants may be added to the solution to minimize nanoparticle aggregation.
[0087] [Centrifugal separation process] The manufacturing method of the present invention preferably includes a centrifugation step in which the nanoparticle-containing liquid is centrifuged and the supernatant liquid is recovered. This involves passing the liquid containing nanoparticles obtained by spark discharge through an ultracentrifuge, allowing the larger nanoparticles to settle, and then recovering the supernatant liquid to selectively recover only the smaller nanoparticles. Furthermore, this step can also be expected to disperse any aggregates that have formed from the aggregation of nanoparticles. For example, the CS150NX ultracentrifuge from Koki Holdings can be used for the centrifugation step. The supernatant liquid in which the nanoparticles are dispersed can be considered as a dispersed colloid.
[0088] When separating by centrifugation, it is preferable to use a centrifuge with a relative centrifugal acceleration of 100 kG (100,000 G) or more, given that the nanoparticles obtained by the manufacturing method of the present invention are extremely small. A relative centrifugal acceleration of 200 kG or more is more preferable, 400 kG or more is more preferable, and 600 kG or more is even more preferable. The centrifugation time is also preferable, depending on the acceleration, but 1 minute or more is preferable, 5 minutes or more is more preferable, 10 minutes or more is even preferable, and 15 minutes or more is even preferable. The centrifugation conditions are set appropriately considering the product of these relative centrifugal accelerations and centrifugation time. For nanoparticles with smaller particle sizes to be obtained, a higher acceleration and a longer time are preferable. There is no upper limit to the relative centrifugal acceleration, but it may be 2,000 kG or less, 1,000 kG or less, or 800 kG or less. The centrifugation time may be 120 minutes or less, 90 minutes or less, 60 minutes or less, or 30 minutes or less.
[0089] As described above, the manufacturing method of the present invention can produce various types of nanoparticles by combining electrodes 101 and 102 and liquid 202. Furthermore, by setting the current within a predetermined range, extremely small nanoparticles can be produced more efficiently than conventional methods. In addition, it is a manufacturing method that requires low electrical energy and does not require high vacuum or high voltage power supplies, thus reducing equipment investment. Moreover, the equipment is easy to design and manage, and mass production is easy depending on the size of electrodes 101 and 102 and container 201, making the manufacturing method of the present invention suitable for mass production of high-quality nanofunctional materials.
[0090] [nanoparticles] The nanoparticles of the present invention have an average particle size of 2.0 nm or less as measured by dynamic light scattering, and include one selected from the group consisting of metals, metal compounds, and semiconductors.
[0091] In the present invention, nanoparticles are particles ranging in size from nanoscale to sub-nanometer. Nanoparticles produced by the manufacturing method of the present invention are formed as particles containing elements mainly used as electrodes. The nanoparticle-containing liquid in the present invention is a liquid containing the nanoparticles of the present invention. For example, it is a dispersion (solution) in which nanoparticles formed by the manufacturing method of the present invention are dispersed in a liquid.
[0092] The average particle size of the nanoparticles of the present invention is measured by dynamic light scattering. Dynamic light scattering can be performed, for example, using the "Particle Size / Molecular Weight Measurement System ELSZ-2000S" from Otsuka Electronics Co., Ltd.
[0093] [TEM observation] Transmission electron microscopy (TEM) observations were performed using a Philips high-resolution electron microscope (HR-TEM), F20. The resolution of this TEM device is approximately 1 nm, although this can vary depending on how it is used.
[0094] [Dynamic light scattering method] In the photon correlation method of dynamic light scattering, the initial gradient (attenuation constant Γ) of the autocorrelation function is determined by analyzing the autocorrelation function using the cumulant method. By analyzing this, the speed of the typical Brownian motion of particles in the liquid sample (diffusion coefficient D) can be determined, and by substituting this into the Einstein-Stokes equation, the average particle diameter can be obtained. The standard deviation is the standard deviation (spread) of each peak obtained from the particle size distribution. The difference between the particle size of each peak obtained above and the particle size of each bar graph is found, squared, and then multiplied by the frequency. Dividing this sum by the sum of the frequencies of each peak and taking the square root gives the standard deviation of each peak. In a Gaussian particle size distribution, the minimum particle size is called D0, the peak value is called D50, the maximum value is called D100, and the 90% value between the minimum and maximum is called D90. Also, the minimum limit of the particle size measurement range listed in the catalog for the particle size / molecular weight measurement system ELSZ-2000S is 0.6 nm. According to Otsuka Electronics Co., Ltd., this guarantees values down to 0.6 nm, and if a value lower than that is displayed, it indicates that the average particle size is less than 0.6 nm.
[0095] The average particle size of the nanoparticles of the present invention may be set according to the type of particle, but can be 2.0 nm or less, preferably 1.7 nm or less, and may also be 1.5 nm or less, 1.4 nm or less, or 1.2 nm or less. Furthermore, depending on the type of constituent elements, it may be set to 1.0 nm or less, 0.8 nm or less, 0.7 nm, or 0.6 nm or less as appropriate. The lower limit of the average particle size can also be set appropriately according to the type and size of the elements constituting each nanoparticle, and may be 0.08 nm or more, 0.1 nm or more, or 0.2 nm or more. The average particle size can be the average particle size of the number of particles measured by dynamic light scattering.
[0096] The nanoparticles of the present invention are preferably monodisperse. Monodisperse nanoparticles are defined as having only one peak when plotted on a graph with particle size and number distribution as axes using dynamic light scattering. This peak is defined as any number of nanoparticles exceeding half the number distribution of the largest peak.
[0097] The nanoparticles of the present invention preferably have a small particle size deviation. The nanoparticles of the present invention have an extremely narrow variation from the average particle size and are easy to handle as they consistently contain a large amount of small particles. The deviation value may be 5 or less, 3 or less, 1 or less, 0.7 or less, 0.5 or 0.2 or less, as the standard deviation of the particle size (nm).
[0098] The nanoparticles of the present invention preferably have a small 90% particle size (D90) based on the number distribution. Thus, the nanoparticles of the present invention are obtained consisting of substantially only extremely small particles, and are easy to handle as the probability of coarse particles being present is extremely low. D90 is preferably 3 times or less the average particle size, more preferably 2.5 times or less, and even more preferably 2.0 times or less. Depending on the type of nanoparticle and the average particle size, D90 may be set to 5.0 nm or less, 4.0 nm or less, 3.0 nm or less, 2.0 nm or less, 1.5 nm or less, 1.0 nm or less, 0.8 nm, 0.6 nm or less.
[0099] In dynamic light scattering (TEM) particle size measurement, if nanoparticles are condensed into clumps and not dispersed, the measurement tends to focus on the size of the aggregate. Therefore, the minimum value is close to the size of a single nanoparticle. In contrast, TEM observation allows for the determination of the shape and size of individual nanoparticles. Consequently, if the particle size measured by dynamic light scattering is consistent with, or smaller than, the particle size measured by TEM observation, it is judged to be the particle size of a single nanoparticle. However, TEM observation has limitations in resolution, and with the Philips high-resolution electron microscope (HR-TEM), F20 used in this experiment, accurate particle size measurement of particles smaller than approximately 2 nm is difficult. However, the minimum particle size measurement range listed in the catalog for the ELSZ-2000S dynamic light scattering particle size / molecular weight measurement system used in this experiment is 0.6 nm. The resolution of the Philips high-resolution electron microscope (HR-TEM), F20 is approximately 1 nm, and particles smaller than 2 nm can be observed, but the particle size cannot be accurately determined; therefore, for particles smaller than that, dynamic light scattering is the only option.
[0100] [Elements that make up nanoparticles] The nanoparticles of the present invention contain metallic and / or metalloid or semiconductor elements. These metals and semiconductors contain at least the elements found in the materials used for electrodes as described in the manufacturing method of the present invention. In addition to the principle of electrode-derived elements, liquid-derived elements may also be included as appropriate. The elements constituting these nanoparticles, including electrode and liquid-derived elements, are those described in the manufacturing method of the present invention described above.
[0101] The nanoparticles of the present invention may contain, as constituent elements, any element selected from the group consisting of noble metals, base metals, and alloys. Alternatively, they may consist substantially of any element selected from the group consisting of noble metals, base metals, and alloys. These noble metals, base metals, and alloys are those described in the manufacturing method of the present invention described above. Similarly, the nanoparticles of the present invention may also be semiconductor particles.
[0102] In the field of catalysts, the development of high-performance catalysts such as platinum (Pt), rosium (Rh), and palladium (Pd) is one of the important issues related to industrial infrastructure, including the environment, resources, and energy. In particular, the development of high-performance precious metal catalysts is an urgent issue in exhaust gas catalysts and fuel cell catalysts due to their rarity and importance, and the creation of new nanoparticles is indispensable for this task. Pt, Pd, and Ru are used as exhaust gas catalysts, Pt and its alloys are used as fuel cell catalysts, and pure precious metals are used in hydrogen and oxidation reactions. In addition, Pd is used as a catalyst in the manufacturing process of IC and LSI semiconductors.
[0103] In catalysts, reducing particle size increases surface area, significantly improving reactivity and catalytic properties. Therefore, synthesizing small-particle nanoparticles is a crucial challenge.
[0104] [Gold (Au) nanoparticles] The nanoparticles of the present invention can be gold nanoparticles, which are substantially composed of gold as a constituent element. Preferably, the gold nanoparticles have an average particle size of 0.7 nm or less as determined by dynamic light scattering. More preferably, they may be 0.65 nm or less, 0.60 nm or less, or 0.50 nm or less. The lower limit does not need to be specifically defined and may be set based on the size of the gold element alone. Regarding gold nanoparticles, the particle size of Undecagold is said to be approximately 0.82 nm. The nanoparticles of the present invention are provided with an average particle size smaller than that of Undecagold and can be made to have superior reactivity and other properties compared to Undecagold. The supernatant liquid in which these nanoparticles are dispersed can be considered as a dispersed colloid.
[0105] [Palladium (Pd) nanoparticles] The palladium nanoparticles of the present invention can be palladium (Pd) nanoparticles, which are substantially composed of palladium as a constituent element. The Pd nanoparticles preferably have an average particle size of 1.7 nm or less as determined by dynamic light scattering. More preferably, they may be 1.6 nm or less, 1.5 nm or less, or 1.4 nm or less. The lower limit does not need to be specifically defined and may be set based on the size of the palladium element alone or its intended use. For example, the lower limit of the average particle size of Pd nanoparticles may be 0.5 nm or more, 0.8 nm or more, or 1.0 nm or more. The nanoparticles of the present invention are provided with a smaller average particle size than conventional Pd nanoparticles and can exhibit superior reactivity. The supernatant liquid in which these nanoparticles are dispersed can be considered a dispersed colloid.
[0106] [Platinum (Pt) nanoparticles] The palladium nanoparticles of the present invention can be platinum (Pt) nanoparticles, which are substantially composed of platinum as a constituent element. The Pt nanoparticles preferably have an average particle size of 1.7 nm or less as measured by dynamic light scattering. More preferably, they may be 1.6 nm or less, 1.5 nm or less, or 1.4 nm or less. The lower limit does not need to be specifically defined and may be set based on the size of the platinum element alone or its intended use. For example, the lower limit of the average particle size of Pd nanoparticles may be 0.5 nm or more, 0.8 nm or more, or 1.0 nm or more. The nanoparticles of the present invention are provided with a smaller average particle size than conventional Pt nanoparticles and can exhibit superior reactivity. The supernatant liquid in which these nanoparticles are dispersed can be considered a dispersed colloid.
[0107] Quantum dots, such as CdSe quantum dots, can emit light from blue-green to red (500-650nm) by changing their particle size from approximately 3nm to 5nm. Generally, the particle size of quantum dots can be controlled by the temperature or reaction time of the thermal decomposition reaction of the organometallic compound used in synthesis. The band gap of quantum dots also depends on the type of semiconductor. Currently, quantum dots that emit light from the visible to near-infrared (400-2000nm) range can be synthesized using semiconductors such as ZnSe, CdS, CdSe, CdSeTe, PbS, PbSe, Si, and C. Thus, there is a need for efficient methods for manufacturing smaller nanoparticles. This invention provides a manufacturing method that can efficiently produce such nanoparticles. If the size of these quantum dots can be reduced to 3nm or less, emission from the ultraviolet range will become possible, dramatically expanding the range of applications.
[0108] [Morphology of nanoparticles] The nanoparticles of the present invention can be used as nanoparticles dispersed in a liquid, or as a mixed composition in which they are combined with other materials according to the application, such as in the form of a paste.
[0109] [Applications of nanoparticles] Nanoparticles offer superior surface area, reactivity, catalytic properties, and magnetism compared to bulk materials and powders. Therefore, they can be used in a wide range of fields, including environmental protection, IT, printing, and medicine, as catalysts, magnetic materials, battery materials, semiconductor materials, nanodots, photoelectric materials, medical materials, pharmaceutical materials, health foods, and dyes.
[0110] [Examples] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples unless its essence is changed.
[0111] [Example 1] Example of palladium nanoparticles The manufacturing process was carried out using a configuration similar to the manufacturing apparatus shown in Figure 1. Two cylindrical palladium electrodes (99.95% purity, 3 mm in diameter), which are elemental palladium, were immersed in a 200 mL beaker containing water as the liquid, with the distance between the tips of the electrodes being approximately 0.5 mm. While vibrating the electrodes, a spark discharge was induced between the palladium electrodes by repeatedly supplying a current from a power source, generating plasma repeatedly and synthesizing palladium nanoparticles. When testing the effect of the presence or absence of a surfactant, one drop of Kao Corporation's "Kyukyutto" (registered trademark) was added to the liquid in the beaker as the surfactant.
[0112] The power supply unit 30 is designed using a pulse generator and resistors, as shown in Figure 2. There are two types of pulse generators: a conventionally known older type (power supply (1)) and an improved new type (power supply (2)), which differ in voltage, current rise time, and peak current, as mentioned above. The pulse generator of the new power supply unit 30 can output a square wave voltage with a rise and fall time of 1 μs or less, a width of about 100 μs, a peak voltage of about 160 V to 250 V, and a frequency of 5 kHz, as shown in Figure 3. In addition, the internal resistance is about 10 Ω for the older type, compared to about 2 Ω for the new type, and the peak current is 50 A or less for the older type, compared to 80 A to 125 A or more for the new type, with a current width of about 10 μs to 50 μs.
[0113] Figure 3 shows an example of voltage waveform measurement using the new power supply (2) generator. A repeating square wave with a rise and fall time of 0.5 μs or less, an interval of 100 μs, and a period of 5 kHz is obtained.
[0114] In the experiment, the generator was set to voltage values of 60V, 100V, and 200V with power supply (1), and to voltage values of 15V and 40V with power supply (2). In this specification, the values shown as voltages for power supply (1) and power supply (2) are the set voltage values for power supply (1) and power supply (2), respectively, and not the measured output voltage values of power supply (1) and power supply (2). Approximately 0.5g of palladium nanoparticles can be obtained by manufacturing in one hour, based on dry weight. For the shape measurements and other procedures described below, samples prepared with a manufacturing time of approximately one hour were used.
[0115] Figure 4 (Figures 4A to 4E) shows the current waveforms when using palladium electrodes. Figures 4A, 4B, and 4C show the waveforms from power supply (1). Figures 4D and 4E show the waveforms from power supply (2).
[0116] In power supply (1), the rise time is approximately 15 μs or less for 60V, 100V, and 200V, with two or one stage, and the peak current is 50 A or less. In power supply (2), at 15V and 40V, the rise time is 10 μs to 20 μs or less, and the peak current is 80 A to 125 A or more. In this specification, the values shown as current for power supply (1) and power supply (2) are the measured output currents of power supply (1) and power supply (2). The current values are measured by a current transformer (Pearson Electronics Model 4100). The interval is basically 100 μs, but it may be slightly faster or irregular depending on the shaping circuit and discharge characteristics. Here, the current value depends on the type of electrode and the individual discharge phenomenon, so the current value is not necessarily proportional to the voltage.
[0117] [Optical observation / photography] Figure 5 (Figures 5A to 5D) shows photographs of glass containers containing palladium nanoparticle-containing liquid. Figure 5A: Power supply (1) 60V, Figure 5B: Power supply (1) 100V, Figure 5C: Power supply (1) 200V, from left to right: Day 0, Day 1, Day 2, Day 3. Figure 5D: Power supply (2) 5V to 40V, after more than six months.
[0118] With power supply (1), nanoparticles gradually settle each day at any voltage, and by the third day, most of the particles have settled. However, the settling of Brown particles slows down as the voltage increases. This suggests that the particle size of the suspended particles becomes smaller at higher voltages (Figures 5A-5C). With power supply (2) at 15V, the particles remain dispersed and suspended even after six months (Figure 5D). This suggests that the particle size of the palladium nanoparticles synthesized with power supply (2) is significantly smaller than that of (1). The supernatant liquid in which these nanoparticles are dispersed can be considered a dispersed colloid.
[0119] In the manufacturing method of the present invention, in order to recover small-particle nanoparticles, the nanoparticle-containing liquid produced in Example 1 was subjected to a centrifugation process. The centrifugation process was performed using a Koki Holdings CS150NX ultracentrifuge. In this case, eight 4cc centrifuge tubes were used. The centrifugation was performed at an acceleration of 600kG for 10 minutes.
[0120] [TEM observation] TEM observation was performed to directly visualize the morphology and size of the nanoparticles. The TEM used was the Tecnai F20 from FEI. The results of palladium nanoparticle observation by FE-TEM are shown in Figures 6A to 6E. The results are summarized in Table 1.
[0121] In samples obtained using power supplies (1) with a peak current of 50A or less, as seen in Figures 6A-6D, the average particle size was 3 nm or larger, and no particles smaller than 2 nm were obtained. In contrast, in samples obtained using power supplies (2) with a peak current of 125A or more, as seen in the TEM images in the upper right and lower left of Figure 6E, although the exact dimensions could not be determined, numerous nanoparticles with a particle size of 2 nm or less were observed (arrows in the figure). Note that the nanocrystals larger than 2 nm in the 40V image were used for TEM focusing. Here, the nanoparticles were confirmed to be palladium with a face-centered cubic lattice structure by diffraction grating analysis.
[0122] The trend is that the higher the voltage, the smaller the average particle size of the aggregated sample, and furthermore, the average particle size is smaller when a surfactant is used. This suggests that higher energy input leads to finer, more micronized particles. It also suggests that the surfactant prevents aggregation.
[0123] [Dynamic light scattering method] For particle size measurement using dynamic light scattering, we used the ELSZ-2000 from Otsuka Electronics Co., Ltd. This device estimates the particle size of nanoparticles in a liquid by measuring the scattered light from a laser beam. The average particle size of palladium nanoparticles in water was measured using dynamic light scattering. The results of the dynamic light scattering particle size measurement of palladium particles are shown in Figure 7 (Figures 7A to 7H). The results are summarized in Table 1.
[0124] [Scattering intensity distribution] Figures 7A to 7F show the results of measuring the particle size of samples obtained using power supply (1) with a peak current of 50A or less by dynamic light scattering, while Figures 7G to 7I show the results of measuring the particle size of samples obtained using power supply (2) with a peak current of 125A or more by dynamic light scattering. The particle size of the samples obtained using power supply (1) without the centrifugation step (Figures 7A to 7D) was orders of magnitude larger than that obtained using power supply (2) (Figures 7F to 7H), and TEM observation revealed nanoparticles with an average particle size of 3nm to 7nm, suggesting that the nanoparticles aggregated to form aggregates. However, no particles were observed in the particle size of the sample obtained using power supply (1) after the centrifugation step (Figure 7E). This is thought to be because the nanoparticle aggregates obtained using power supply (1) settled during the centrifugation step and were not present in the supernatant, thus the target extremely small nanoparticles were not present. On the other hand, for the samples obtained using power supply (2) after the centrifugation step, measurements were performed three times on the same sample to ensure reliability. As a result, as can be seen in Figures 7F to 7H, the average particle sizes obtained were 1.4, 1.6, and 1.7 nm. Therefore, it can be concluded that with power supply (1), nanoparticles with an average particle size of 3 nm or more and no nanoparticles of 2 nm or less were obtained, whereas with power supply (2), extremely small nanoparticles with an average particle size of 2 nm or less were obtained. TEM observation of the samples obtained in these centrifugal processing steps revealed particles with an average particle size of 2 nm or less, and 1.4, 1.6, and 1.7 nm can be considered to be the particle sizes of individual nanoparticles.
[0125] [Table 1]
[0126] Table 1 summarizes the measurement results for Pd particle size. In Table 1, under *1, numerous nanoparticles with a particle size of 2 nm or less were observed using FE-TEM observation of power supply (2), but their dimensions could not be precisely determined. The average particle sizes were measured as 1, 4, 1.6, and 1.7 nm using dynamic light scattering.
[0127] Table 1 summarizes the results for palladium nanoparticle particle size obtained by dynamic light scattering and FE-TEM. Optical observations showed that nanoparticles produced by power source (1) almost completely settled within about 3 days, while nanoparticles produced by power source (2) remained suspended even after 6 months. This indicates that the nanoparticles produced by power source (2) are significantly smaller than those produced by (1).
[0128] TEM observation revealed that the sample from power source (1) had an average particle size of approximately 3 nm to 7 nm. However, while the size of the sample from power source (2) could not be determined due to its small size, nanoparticles with an average particle size of 2 nm or less were observed. Dynamic light scattering measurements showed that, for the sample from power source (1), only the particle size of aggregates could be measured without the centrifugation process. However, for the nanoparticles from the sample from power source (2) that underwent the centrifugation process, the average particle size of the number distribution was 1.4 nm to 1.7 nm based on three measurements, indicating a significantly smaller particle size. Therefore, it was concluded that nanoparticles of 2 nm or less were obtained using power source (2).
[0129] The difference in particle size is thought to be related to the fact that, according to the current waveform flowing through the electrodes, the older power supply (1) has a rise time of about 20 μs in two or one stage for both 60V and 200V, with a peak current of 50A or less. In contrast, the newer power supply (2) has a current of 80A to 125A or more. As mentioned earlier, this is because the peak current value of the newer power supply (2) is more than twice that of the older power supply (1), resulting in an extremely high temperature rise and rapid plasma generation, which generates a large number of ions. The higher the temperature, the more uniform nucleation is promoted by cooling with the surrounding liquid, and the intense rapid cooling effect suppresses crystal growth, resulting in the generation of significantly more small clusters. It is thought that these clusters are frozen as they are by rapid cooling, yielding a large quantity of extremely small nanoparticles.
[0130] These conclusions show that nanoparticles with a particle size of 2.0 nm or less can be efficiently synthesized by using power supply (2) with a voltage rise and fall time of 1 μs or less, applying a repeating current to the electrodes with a peak current of 80 A to 125 A or more and a rise time of 10 μs to 20 μs or less. In this process, the centrifugation step is important for selecting only the very small nanoparticles and for dispersing aggregates.
[0131] [Example 2] Example of gold nanoparticles Gold nanoparticles were produced using the same apparatus as that used for the production of palladium in Example 1. Two cylindrical gold electrodes (99.99% purity, 3 mm in diameter), which are elemental gold, were immersed in a 200 mL beaker of water with a distance of approximately 0.5 mm between the tips of the electrodes. While vibrating the electrodes, a spark discharge was induced between the gold electrodes by repeatedly supplying a current from a power source, generating plasma repeatedly and synthesizing gold nanoparticles. The power supply unit 30 was the same as that used in Example 1.
[0132] The generator's peak voltage was set to 60V, 100V, and 200V using power supply (1), and then set to 200V using power supply (2).
[0133] Approximately 2.1g of gold nanoparticles (dry weight) can be obtained by manufacturing them in one hour. The following shape measurements were performed using samples prepared in about one hour.
[0134] Figures 8A to 8D show the current waveforms when gold electrodes are used. Figures 8A to 8C show the waveforms with power supply (1). Figure 8D shows the waveform with power supply (2). With power supply (1), the rise time is 10 to 20 μs or less for 60V, 100V, and 200V, in two or one stage, and the peak current is 50A or less. With power supply (2), the rise time is 20 μs or less and the peak current is 125A or more. The interval is basically 100 μs, but it can be slightly faster or irregular depending on the shaping circuit and discharge characteristics. Here, the current value depends on the type of electrode and the individual discharge phenomenon, so the current value is not necessarily proportional to the voltage.
[0135] [Observation / Photography] Figures 9A to 9D are photographs of glass containers holding a liquid containing gold nanoparticles. Figure 9A: Power supply (1) 60V, Figure 9B: Power supply (1) 100V, Figure 9C: Power supply (1) 200V, from left to right: Day 0, Day 1, Day 2, Day 3. Figure 9D: Power supply (2) 200V, several months elapsed.
[0136] The general trend is that the higher the voltage, the longer the nanoparticles remain suspended. In other words, the higher the voltage, the slower the settling velocity and the smaller the particle size of the suspended particles.
[0137] With power supply (1), nanoparticles gradually settle each day at any voltage, and by the third day, most of the particles have settled. However, the settling of Brown particles slows down as the voltage increases. This suggests that the particle size of the suspended particles becomes smaller at higher voltages (Figures 9A-9C). With power supply (2) at 15V, the particles remain dispersed and suspended even after several months (Figure 9D). This suggests that the particle size of the gold nanoparticles synthesized with power supply (2) is significantly smaller than that of (1). The supernatant liquid in which these nanoparticles are dispersed can be considered a dispersed colloid.
[0138] In the manufacturing method of the present invention, the nanoparticle-containing liquid of Example 2 was subjected to a centrifugation step to recover small-particle nanoparticles. The centrifugation step was performed using a Koki Holdings CS150NX ultracentrifuge. In this case, eight 4cc centrifuge tubes were used. The centrifugation was performed at an acceleration of 600kG for 10 minutes.
[0139] [TEM] TEM observation was performed to directly visualize the morphology and size of the nanoparticles. The TEM used was the Tecnai F20 from FEI. The results of the FE-TEM observation of gold nanoparticles are shown in Figures 10A to 10C. The results are summarized in Table 2.
[0140] In samples obtained using power supplies (1) with a peak current of 50A or less, as seen in Figures 10A and 10B, the average particle size was 3 nm or larger, and no particles smaller than 2 nm were obtained. In contrast, in samples obtained using power supplies (2) with a peak current of 125A or more, particles smaller than 2 nm were observed, as seen in the lower left image of Figure 10C. When actually operating the TEM, even smaller particles were observed with the naked eye on the monitor. However, these were too small and exceeded the imaging limit of the FE-TEM (approximately 1 nm), making it difficult to record them during imaging. Note that the nanocrystals larger than 2 nm in the 200V image were used for focusing the TEM. Here, the nanoparticles were confirmed to be gold with a face-centered cubic lattice structure by diffraction grating analysis.
[0141] The trend is that the higher the voltage, the smaller the average particle size of the aggregated sample, and furthermore, the average particle size is smaller when a surfactant is used. This suggests that higher energy input leads to finer, more micronized particles. It also suggests that the surfactant prevents aggregation.
[0142] [Dynamic light scattering method] Particle size measurements using dynamic light scattering were performed using the same apparatus as that used for palladium. The results of the dynamic light scattering particle size measurements for gold nanoparticles are shown in Figure 11. The results are summarized in Table 2.
[0143] [Scattering intensity distribution] Figures 11A to 11E show the results of measuring the particle size of samples obtained using power supply (1) with a peak current of 50A or less by dynamic light scattering, while Figures 6F to 6H show the results of measuring the particle size of samples obtained using power supply (2) with a peak current of 125A or more by dynamic light scattering. The particle size of samples obtained using power supply (1) without the centrifugation step (Figures 11A to 11D) was orders of magnitude larger than those obtained using power supply (2) (Figures 11F to 11H), except for Figure 11D. TEM observations revealed nanoparticles with an average particle size of approximately 5 nm or larger, suggesting that the nanoparticles aggregated to form aggregates. However, the particle size of the sample obtained using power supply (1) after the centrifugation step (Figure 6E) was 10.6 nm on average. This also suggests some aggregation. On the other hand, for the sample obtained using power supply (2) after the centrifugation step, measurements were performed three times on the same sample to ensure reliability. As a result, the average particle size was ultimately 0.2 nm in all cases. The standard deviations were 0.1nm to 0.5nm, and for 90D it was 0.6nm, confirming that they were significantly smaller. However, the minimum limit of the measurement range in the catalog for this instrument is 0.6nm. This means that the value is guaranteed down to 0.6nm, and if a value lower than that is displayed, it indicates that the average particle size is less than 0.6nm. Therefore, it was determined that the average particle size was less than 0.6nm. Thus, it was determined that while no nanoparticles with an average particle size of 3nm or more and less than 2nm were obtained with power supply (1), extremely small nanoparticles with an average particle size of less than 0.6nm were obtained with power supply (2). The particle sizes of the samples obtained in these centrifugal processing steps were confirmed by TEM observation to be particles with an average particle size of less than 2nm, which can be said to be the particle size of each individual nanoparticle less than 0.6nm.
[0144] [Table 2]
[0145] Table 2 summarizes the measurement results for gold particle size. In Table 2, under *1, FE-TEM observation of power supply (2) revealed numerous nanoparticles with a particle size of 2 nm or less, but the exact dimensions could not be determined. The average particle size was measured to be less than 0.6 nm by dynamic light scattering.
[0146] Table 2 summarizes the results for the particle size of gold nanoparticles obtained by dynamic scattering light and FE-TEM. Optical observations showed that nanoparticles produced by power source (1) almost completely settled within about 3 days, while nanoparticles produced by power source (2) remained suspended without settling even after several months. This indicates that the nanoparticles produced by power source (2) are significantly smaller than those produced by (1).
[0147] TEM observation revealed that the sample from power source (1) had an average particle size of approximately 5 nm. However, while nanoparticles smaller than 2 nm could be visually confirmed on the monitor for the sample from power source (2), they were too small to image due to the limitations of the TEM instrument. Dynamic light scattering measurements showed that, for the sample from power source (1), only the particle size of aggregates could be measured without the centrifugation process. However, for the nanoparticles from the sample from power source (2) that underwent the centrifugation process, the average particle size of the number distribution was less than 0.6 nm based on three measurements, indicating a significantly smaller size. Therefore, it was concluded that nanoparticles smaller than 0.6 nm were obtained using power source (2).
[0148] This difference in particle size is thought to be related to the fact that, according to the current waveform flowing through the electrodes, the older power supply (1) has a rise time of about 20 μs in two or one stage for both 60V and 200V, with a peak current of 50A or less. In contrast, the newer power supply (2) has a current of 80A to 125A or more. As mentioned earlier, this is because the peak current value of the newer power supply (2) is more than twice that of the older power supply (1), resulting in an extremely high temperature rise and rapid plasma generation, which generates a large number of ions. The higher the temperature, the more uniform nucleation is promoted by cooling with the surrounding liquid, and the intense rapid cooling effect suppresses crystal growth, resulting in the generation of significantly more small clusters. It is thought that these clusters are frozen by the rapid cooling, yielding a large quantity of extremely small nanoparticles.
[0149] Furthermore, while the particle size of palladium was approximately 2 nm or less at 40 V power supply (2), it was reduced to less than 0.6 nm at 200 V gold. This is thought to be because, while welding and other effects occurred with palladium at voltages above 40 V, with gold, the current reached over 125 A and nearly 150 A at 200 V power supply (2), increasing the plasma temperature and pushing the rapid cooling rate to its limits. This further increased the plasma temperature, increasing the number of metal nuclei and thus reducing the particle size even more. It is thought that the particle size of palladium could also be reduced even further by using high voltages such as 200 V power supply (2).
[0150] These conclusions show that nanoparticles with a particle size of less than 0.6 nm can be efficiently synthesized by applying a repeating current to the electrodes using power supply (2), with a voltage rise and fall time of 1 μs or less, a peak current of 80 A to 125 A or more, and a current rise time of 10 μs to 20 μs or less. In this process, the centrifugation step is important for selecting only the very small nanoparticles and for dispersing aggregates.
[0151] [Example 3] Example of platinum nanoparticles The manufacturing process was carried out using a configuration similar to the manufacturing apparatus shown in Figure 1. Two cylindrical platinum electrodes (99.99% purity, 3 mm in diameter), which are elemental platinum, were immersed in a 200 mL beaker containing water as the liquid, with a distance of approximately 0.5 mm between the tips of the electrodes. While vibrating the electrodes, a spark discharge was induced between the platinum electrodes by repeatedly supplying a current from a power source, thereby repeatedly generating plasma and synthesizing platinum nanoparticles. The power supply unit 30 is the same as that used in Example 1.
[0152] In the experiment, the generator's peak voltage was set to 100V using power supply (1) and to 200V using power supply (2).
[0153] Approximately 0.5g of platinum nanoparticles (dry weight) can be obtained by manufacturing them in one hour. The following shape measurements were performed using nanoparticles prepared in about one hour.
[0154] Figures 12A and 12B show the current waveforms when platinum electrodes are used. Figure 12A shows the waveform from power supply (1). Figure 12B shows the waveform from power supply (2).
[0155] In power supply (1), the rise time is 15 μs or less with two or one stage, and the peak current is 50 A or less. In power supply (2), the rise time is 10 μs to 20 μs or less, and the peak current is 125 A or more. The interval is basically 100 μs, but it may be slightly faster or irregular depending on the shaping circuit and discharge characteristics. Here, the current value depends on the type of electrode and the individual discharge phenomenon, so the current value is not necessarily proportional to the voltage.
[0156] In the manufacturing method of the present invention, in order to recover small-particle nanoparticles, the nanoparticle-containing liquid of Example 3 was subjected to a centrifugation step for both samples (1) and (2). The centrifugation step was performed using a Koki Holdings ultracentrifuge CS150NX. In this case, eight 4cc centrifuge tubes were used. The centrifugation was performed at an acceleration of 600kG for 10 minutes.
[0157] [TEM observation] TEM observation was performed to directly visualize the morphology and size of the nanoparticles. The TEM used was the Tecnai F20 from FEI. The results of the FE-TEM observation of platinum nanoparticles are shown in Figures 13A and 13B. The results are summarized in Table 3.
[0158] In samples obtained using power supply (1) with a peak current of 50A or less, the average particle size was 3 nm or larger. In contrast, in samples obtained using power supply (2) with a peak current of 125A or more, particles were not as clearly observed as Pd or gold, but when actually operating the TEM, particles smaller than 2 nm could be observed with the naked eye on the monitor. However, these were too small to exceed the imaging limit of the FE-TEM, making recording difficult during imaging. Note that nanocrystals larger than 2 nm were used for focusing the TEM. Here, the nanoparticles were confirmed to be platinum with a face-centered cubic lattice structure by diffraction grating analysis.
[0159] [Dynamic light scattering method] Particle size measurements using dynamic light scattering were performed using the same apparatus as that used for palladium. The results of the dynamic light scattering particle size measurements for platinum particles are shown in Figure 14. The results are summarized in Table 3.
[0160] [Scattering intensity distribution] Figure 14A shows the results of measuring the particle size of a sample obtained using power supply (1) with a peak current of 50A or less, measured by dynamic light scattering, while Figure 14B shows the results of measuring the particle size of a sample obtained using power supply (2) with a peak current of 125A or more, measured by dynamic light scattering. As can be seen in Figure 14A, the particle size obtained with power supply (1) is orders of magnitude larger than that obtained with power supply (2), and TEM observations show nanoparticles with an average particle size of 3 nm or more, suggesting that the nanoparticles aggregated to form aggregates. On the other hand, as can be seen in Figure 14B, the average particle size of platinum nanoparticles obtained with power supply (2) was 1.4 nm, with a standard deviation of 0.1 nm, and the 90D was 1.7 nm, confirming that they were significantly smaller. Therefore, it can be concluded that power supply (1) did not yield nanoparticles with an average particle size of 3 nm or more and no nanoparticles with an average particle size of 2 nm or less, while power supply (2) yielded extremely small nanoparticles with an average particle size of 2 nm or less. Since TEM observation confirmed that samples obtained through these centrifugal processing steps contain particles with an average particle size of 2 nm or less, it can be said that an average particle size of 1.4 nm is the particle size of nanoparticles. The centrifugal separation process is an important step not only for selecting nanoparticles but also for dispersing aggregates.
[0161] [Table 3]
[0162] Table 3 summarizes the measurement results for Pt particle size. In Table 3, under *1, FE-TEM observation of power supply (2) revealed numerous nanoparticles with a particle size of 2 nm or less, but the exact dimensions could not be determined. Dynamic light scattering measured the average particle size as 1.4 nm.
[0163] TEM observation revealed that the sample from power supply (1) had an average particle size of approximately 3 nm to 5 nm. However, while nanoparticles smaller than 2 nm could be visually confirmed on the monitor for the sample from power supply (2), they were too small to image due to the limitations of the TEM instrument. Dynamic light scattering measurements showed that the particle size from the sample from power supply (1) was larger than that observed by TEM, but the average particle size of the nanoparticles in the number distribution of the sample from power supply (2) that underwent centrifugation was significantly smaller, at 1.4 nm or less. Therefore, it was concluded that nanoparticles smaller than 2 nm were obtained using power supply (2).
[0164] This difference in particle size is thought to be related to the fact that, according to the current waveform flowing through the electrodes, the older power supply (1) has a rise time of about 20 μs in two or one stage for both 60V and 200V, with a peak current of 50A or less. In contrast, the newer power supply (2) has a current of 80A to 125A or more. As mentioned earlier, this is because the peak current value of the newer power supply (2) is more than twice that of the older power supply (1), resulting in an extremely high temperature rise and rapid plasma generation, which generates a large number of ions. The higher the temperature, the more uniform nucleation is promoted by cooling with the surrounding liquid, and the intense rapid cooling effect suppresses crystal growth, resulting in the generation of significantly more small clusters. It is thought that these clusters are frozen by the rapid cooling, yielding a large quantity of extremely small nanoparticles.
[0165] These conclusions show that nanoparticles with a particle size of 2.0 nm or less can be efficiently synthesized by applying a repeating current to the electrodes using power supply (2), with a rise and fall time of 1 μs or less, a current value of 80 A to 125 A or more, and a rise time of 10 μs to 20 μs or less. In this process, the centrifugation step is important for selecting only the very small nanoparticles and for dispersing aggregates. [Industrial applicability]
[0166] The nanoparticles of the present invention can be used in various fields such as environment, IT, printing, and medicine as catalysts, magnetic materials, battery materials, photoelectric materials, medical materials, pharmaceutical materials, and health foods, and are industrially useful. [Explanation of symbols]
[0167] 1...Production equipment, 101,102...Electrode, 201...Container, 202...Liquid, 30...Power supply device, 40...Vibration device. < / b1> < / c1>
Claims
1. A solution of extremely small nanoparticles in which elemental gold nanoparticles with an average particle size of 4.8 nm to 5.4 nm, as measured by TEM, are dispersed in water that does not contain a reducing agent that reduces gold ions.
2. A solution of extremely small nanoparticles in which elemental platinum nanoparticles with an average particle size of 3 nm to 10 nm, as measured by TEM, are dispersed in water that does not contain a reducing agent that reduces platinum ions.
3. A solution of extremely small nanoparticles in which elemental palladium nanoparticles with an average particle size of 3.3 nm to 6.2 nm, as measured by TEM, are dispersed in water that does not contain a reducing agent that reduces palladium ions.
4. Ultra-small elemental gold nanoparticles with an average particle size of 4.8 nm to 5.4 nm as measured by TEM, and which do not contain a reducing agent that reduces gold ions.
5. Platinum elemental nanoparticles with an average particle size of 3 nm to 10 nm or less, as measured by TEM, and which do not contain a reducing agent that reduces platinum ions.
6. Ultra-small palladium nanoparticles having an average particle size of 3.3 nm to 6.2 nm as measured by TEM, and which do not contain a reducing agent that reduces palladium ions.
Citation Information
Patent Citations
NANO particle, NANO particle production method and NANO particle production device
JP2012167335A
Production method of metal nanoparticle dispersion
JP2019094541A